Orexins contribute to restraint stress-induced cocaine relapse by endocannabinoid-mediated disinhibition of dopaminergic neurons - Li-Wei Tung (Nature Portfolio, 2016)
Stress is a major cause of relapse to cocaine seeking behaviour. Tung et al. show that orexin mediates stress-induced reinstatement of cocaine seeking behaviour in mice by endocannabinoid-dependent disinhibition in the ventral tegmental area.